Prospective observational study on the safety of an original fiducial marker insertion for radiotherapy in gynecological cancer by a simple method. (28th October 2019) - Sekii, Shuhei; Tsujino, Kayoko; Kubota, Hikaru; Yamaguchi, Satoshi; Kosaka, Kengo; Miyazaki, Shuichiro; Sulaiman, Nor Shazrina; Matsumoto, Yoko; Ota, Yosuke; Soejima, Toshinori; Sasaki, Ryohei
ABSTRACT: Our observational study aimed to verify the safety of our original titanium fiducial markers in gynecological cancer by using a simple insertion method. We prospectively evaluated the safety in patients with gynecological cancer who had undergone our insertion procedure of the titanium markers. The decision to implant a titanium marker was at the discretion of each radiation oncologist. The fiducial markers were manufactured by severing ligating clips for surgery into 3–6 mm pieces and were sterilized thereafter. We inserted an 18-gauge injection needle containing the marker before the marker was extruded by a 22-gauge Cattelan needle or shape memory alloy wire into the tumor or tissues close to the tumor. Severe complications within 3 months after implantation were scored according to the National Cancer Institute's Common Terminology Criteria for Adverse Events version 4.0. Between August 2016 and December 2018, we enrolled 46 patients. Of 46, 44 underwent implantation. The median age was 58.5 years. The most common primary site was the cervix. Two patients experienced detachment of the markers after implantation. No Grade 3 or higher level of complications was observed. Our simple insertion technique for original titanium fiducial markers was well-tolerated.